Factors of workplace environment that affect employee’s performance at Ministry Of Human Resource in Muar / Arina Mastura Mohamad - Mohamad, Arina Mastura (Faculty of Business and Management, 2014)
Factors of workplace environment play an important role towards the employees’ performance. The factors of workplace environment give an immense impact to the employees’ either towards the negative or positive results. By having a proper workplace environment, it helps in reducing the number of absenteeism and thus can increase the employees’ performance which will leads to the increasing number of productivity at the workplace. In this research, several factor of the workplace environment that affects the employees’ performance.